(untitled) (The Review of Diabetic Studies, 2023)
The pancreas arises from Pdx1-expressing progenitors in developing foregut endoderm in early embryo. Expression of Ngn3 and NeuroD1 commits the cells to form endocrine pancreas, and to differentiate into subsets of cells that constitute islets of Langerhans. β-cells in the islets transcribe gene-encoding insulin, and subsequently process and secrete insulin, in response to circulating glucose. Dysfunction of β-cells has profound metabolic consequences leading to hyperglycemia and diabetes mellitus. β-cells are destroyed via autoimmune reaction in type 1 diabetes (T1D). Type 2 diabetes (T2D), characterized by impaired β-cell functions and reduced insulin sensitivity, accounts for 90% of all diabetic patients. Islet transplantation is a promising treatment for T1D. Pluripotent stem cells provide an unlimited cell source to generate new β-cells for patients with T1D. Furthermore, derivation of induced pluripotent stem cells (iPSCs) from patients captures “disease-in-a-dish” for autologous cell replacement therapy, disease modeling, and drug screening for both types of diabetes. This review highlights essential steps in pancreas development, and potential stem cell applications in cell regeneration therapy for diabetes mellitus